Attentatives Kapital bei Mädchen in MINT - Reutlinger, Marold (Journal für Begabtenförderung, 2013)

Begabtenförderung und Lernumwelten: Soziotope als Rahmenbedingungen der MINT-Förderung von Mädchen und Frauen - Reutlinger, Marold; Buschhaus, F; Groß, C; Hopp, Manuel; Werner, K; Ziegler, Albert (Handbuch der Entwicklungspsychologie des Talents, 2014)
UnivIS-Import:2015-04-20:Pub.2014.phil.dps.ipsy1.lpsych_2.begabt

(untitled) - Stöger, Heidrun; Sturm, K; Heilemann, M; Pufke, E; Schirner, Sigrun; Reutlinger, Marold; Ziegler, Albert (Österreichisches Zentrum für Begabtenförderung und Begabungsforschung)

CyberMentor: E-Mentoring für begabte Mädchen in MINT - Ziegler, Albert; Stöger, Heidrun; Sturm, K; Heilemann, M; Pufke, E; Schirner, Sigrun; Reutlinger, Marold (Begabung - Wissen - Werte : Wege zur Leistungsexzellenz, 2011)

Domain-Specificity of Educational and Learning Capital: A Study With Musical Talents - Reutlinger, Marold; Pfeiffer, Wolfgang; Stoeger, Heidrun; Vialle, Wilma; Ziegler, Albert (Frontiers in Psychology, 2020)
The Education and Learning Capital Approach (ELCA) has been widely used to investigate talent development. A research gap is the implicit consideration of the domain specificity of educational and learning capital. In an empirical study with 365 school students we investigated the domain specificity of the approach for the domains of school learning and learning to play a musical instrument. At the beginning of the school year, students filled out a version of the Questionnaire for Educational and Learning Capital (QELC) for both domains and also responded to other domain-related measures (self-efficacy, grades). Six weeks later, students filled out a learning diary for 1 week in which they reported their activities on an hourly basis and responded to questions concerning these activities. Based on the Sociotope Approach this procedure helped to identify times in which students actually practiced their musical instrument, times that students could potentially practice their musical instrument (objective action space), and times that students would be expected to practice their musical instrument (normative action space). Three hypotheses were tested and could be supported. First, the availability of educational and learning capital for school learning and learning an instrument differed. Second, a confirmatory factor analysis supported the factorial validity of the domain-specific capital measurements. Third, domain-congruent correlations were mostly higher than domain-incongruent correlations, i.e., the availability of educational and learning capital for school learning correlated more closely with variables related to school learning than with variables related to learning a musical instrument. Similarly, the availability of the capitals for learning a musical instrument correlated more closely with variables related to learning a musical instrument.
CRIS-Team Scopus Importer:2020-10-23
Keywords: domain specificity; educational capital; learning capital; music; talent development

Elterliche Gestaltung von infrastrukturellen Soziotopen bei Kindern im Kindergartenalter - Reutlinger, Marold; Ballmann, Anke (Journal für Begabtenförderung, 2016)

Erfolgreich in MINT: Mentoring für Mädchen und Frauen - Stöger, Heidrun; Ziegler, Albert; Greindl, Teresa; Heilemann, M; Neubauer, Tanja; Reutlinger, Marold; Schirner, Sigrun; Sturm, K (Häuser, 2012)
UnivIS-Import:2015-04-02:Pub.2012.phil.dps.ipsy1.lpsych_2.erfolg

Gifted education as a lifelong challenge. Essays in honor of Franz J. Moenks (PSYNDEXalert) - Ziegler, Albert; Fischer, C; Stöger, Heidrun; Reutlinger, Marold (Lit, 2012)

Gifted education as a lifelong challenge : essays in honour of Franz J. Mönks - Ziegler, Albert; Fischer, Christian; Stöger, Heidrun; Reutlinger, Marold (Lit, 2012)

Göçmen kökenlı üstün zekali çocuklar: Göçmen kökenlı aılelere, öğretmenlere ve eğıtımcılere yönelık bılgılendırme - Reutlinger, Marold; Leana-Tasçilar, MarilenaZ.; Ziegler, Albert (2015)

Hochbegabung und Migrationshintergrund: Informationen für Eltern und Pädagogen von Kindern mit Migrationshintergrund - Reutlinger, Marold; Leana-Tasçilar, MarilenaZ.; Ziegler, Albert (2015)

How Desirable Are Gifted Boys for Girls, and Gifted Girls for Boys? Results of a Chatroom Study - Ziegler, Albert; Fidelman, Marina; Reutlinger, Marold; Neubauer, Tanja; Heilemann, M (Australasian journal of gifted education, 2011)

Implicit personality theories on the modifiability and stability of the action repertoire as a meaningful framework for individual motivation: A cross-cultural study - Ziegler, Albert; Fidelman, Marina; Reutlinger, Marold; Vialle, W; Stöger, Heidrun (High ability studies, 2010)

Lisrel: Dorsch - Lexikon der Psycholgoie - Reutlinger, Marold (Dorsch - Lexikon der Psychologie, 2013)

Matlab: Dorsch – Lexikon der Psychologie - Reutlinger, Marold (Dorsch - Lexikon der Psychologie, 2013)

Mplus: Dorsch – Lexikon der Psychologie - Reutlinger, Marold (Dorsch - Lexikon der Psychologie, 2013)

Nachhilfe: Dorsch – Lexikon der Psychologie - Reutlinger, Marold (Dorsch - Lexikon der Psychologie, 2013)

Parental goal orientations for their kindergarten children: Introductiong the Nuremberg Parental Goal Oriantiation Scales (NuPaGOS) - Reutlinger, Marold; Ballmann, Anke; Vialle, W; Zhang, Zhitian; Ziegler, Albert (Psychological Test and Assessment Modeling, 2015)

Possibilities of School-Based Mentoring - Reutlinger, Marold (Gifted education as a lifelong challenge : essays in honour of Franz J. Mönks, 2012)

SAS: Dorsch – Lexikon der Psychologie - Reutlinger, Marold (Dorsch - Lexikon der Psychologie, 2013)

Soziotope als konstitutive Rahmenbedingungen der MINT-Foerderung von Maedchen und Frauen. Sociotopes ad constitutive framework conditions for promotion of girls and women in domains of mathematics, computer science, sciences, and technology - Ziegler, Albert; Reutlinger, Marold; Hering, Eva Marie (Maedchen und Frauen in MINT. Bedingungen von Geschlechtsunterschieden und Interventionsmoeglichkeiten., 2012)
Keywords: *Educational Programs; *Human Females; *Mathematics; *Participation; *Sciences; *Social Environments; 35]; Bildungsprogramme (focus); Computer Science; Computerwissenschaft; Curricula; Bildungsprogramme und Lehrmethoden [3530; Frauen (focus); Learning Environment; Lernumgebung; Mathematics Education; Mathematik (Wissenschaft) (focus); Mathematikunterricht; Naturwissenschaftlicher Unterricht; Partizipation (focus); Science Education; Soziale Umwelt (focus); Technologie; Technology; Wissenschaften (focus)

Soziotope als konstitutive Rahmenbedingungen der MINT-Förderung von Mädchen und Frauen - Ziegler, Albert; Reutlinger, Marold; Hering, Eva Marie (Mädchen und Frauen in MINT : Bedingungen von Geschlechtsunterschieden und Interventionsmöglichkeiten, 2012)

Statistische Zwillinge/statistische Mehrlinge: Dorsch – Lexikon der Psychologie - Reutlinger, Marold (Dorsch - Lexikon der Psychologie, 2013)

The Environmental Impact - Reutlinger, Marold; Till, Kevin (Talent development & excellence, 2011)

The Impact of Sociotopes on School Achievement - Reutlinger, Marold (Talent Talks, 2010)

Triadisches Interdependenzmodell: Dorsch – Lexikon der Psychologie - Reutlinger, Marold (Dorsch - Lexikon der Psychologie, 2013)

Wie begehrt sind Hochbegabte Jungs bei Mädchen und umgekehrt? - Basar, D; Berger, K; Fidelman, Marina; Finkenzeller, F; Friedrich, D; Gesell, J F; Hübner, P; Meyer, K; Reutlinger, Marold; Seibold, F; Wunderlich, K; Ziegler, Albert (News & science, 2010)